STUDI KEPUSTAKAAN MENGENAI KINERJA GURU BIMBINGAN DAN KONSELING DALAM PERENCANAAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH - Dewita Ramadani; Herdi Herdi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
Schools are formal institutions that are specifically formed to provide education for community members. The direction of the formation of this institution is to provide ease of achieving optimal development of students. To achieve optimal self-development in school institutions is realized by the existence of the field of educational services, one of which is the Guidance and Counseling service in schools. Guidance and counseling is a service provided to students to develop their potential optimally. cooperation is needed between guidance and counseling teachers, homeroom teachers, and also school principals in shaping professional counselor performance, namely by providing facilities and infrastructure, in the form of adequate BK space, and also to improve the performance of guidance and counseling teachers, a counselor must have an undergraduate background in educational guidance and counseling.